The Chinese mafia : organized crime, corruption, and extra-legal protection - Wang, Peng (Oxford : Oxford University Press, 2017)
Utilising individual interviews and focus group discussions, primarily from two Chinese cities, 'The Chinese Mafia' contributes to the understanding of organized crime and corruption in the Chinese context, filling a significant gap in criminological literature, by investigating how extra-legal protectors - corrupt public officials and street gangsters - emerge, evolve and operate in a rapidly changing society. China's economic reforms have been accompanied by a surge of social problems, such as ineffective legal institutions, booming black markets and rampant corruption. This has resulted in the rise of extra-legal means of protection and enforcement: such is the demand for protection that cannot be fulfilled by state-sponsored institutions.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 16, 2017).
Keywords: Mafia -- China; Gangs -- China; Corruption -- China; Crime -- China; True Crime; Social services & welfare, criminology